Specific electrogram characteristics impact substrate ablation target area in patients with scar‐related ventricular tachycardia—insights from automated ultrahigh‐density mapping. (19th January 2021) - Schwarzl, Jana M.; Schleberger, Ruben; Kahle, Ann‐Kathrin; Höller, Alexandra; Schwarzl, Michael; Schaeffer, Benjamin N.; Münkler, Paula; Moser, Julia; Akbulak, Ruken Ö.; Eickholt, Christian; Dinshaw, Leon; Dickow, Jannis; et al.
Abstract: Introduction: Substrate‐based catheter ablation approaches to ventricular tachycardia (VT) focus on low‐voltage areas and abnormal electrograms. However, specific electrogram characteristics in sinus rhythm are not clearly defined and can be subject to variable interpretation. We analyzed the potential ablation target size using automatic abnormal electrogram detection and studied findings during substrate mapping in the VT isthmus area. Methods and Results: Electrogram characteristics in 61 patients undergoing scar‐related VT ablation using ultrahigh‐density 3D‐mapping with a 64‐electrode mini‐basket catheter were analyzed retrospectively. Forty‐four complete substrate maps with a mean number of 10319 ± 889 points were acquired. Fractionated potentials detected by automated annotation and manual review were present in 43 ± 21% of the entire low‐voltage area (<1.0 mV), highly fractionated potentials in 7 ± 8%, late potentials in 13 ± 15%, fractionated late potentials in 7 ± 9% and isolated late potentials in 2 ± 4%, respectively. Highly fractionated potentials (>10 ± 1 fractionations) were found in all isthmus areas of identified VT during substrate mapping, while isolated late potentials were distant from the critical isthmus area in 29%. Conclusion: The ablation target area varies enormously in size, depending on the definition of abnormal electrograms. Clear linking of abnormal electrograms with critical VT isthmus areas during substrate mapping remains difficult due to a lack of specificity rather than sensitivity. However, highly fractionated, low‐voltage electrograms were found to be present in all critical VT isthmus sites.